A atividade de estudo no ensino fundamental conforme a teoria do ensino desenvolvimental de V. Davydov e contribuições de M. Hedegaard: um experimento didático em ciências - Silva, Eliane (2020)
This thesis is linked to the Education Theory and Education Processes line of research in the Post-Graduation Programme at Pontifícia Universidade Católica de Goiás - PUC. The research intended to analyze the organization of teaching through the science study activity, according to Davydov's theory of developmental teaching theory and Hedegaard's contributions. It focuses on the formation of theoretical-scientific thinking in the process of schooling of children and, more specifically, formation of concepts in the early years of elementary school. The objectives were: to investigate the formation and development of theoretical thinking by students of the early years of elementary school. With this approach, the specific objectives were proposed: analyze how science teaching can be organized, for the formation of the concept of "water", focusing on the water cycle, in the early years of elementary school mediated by the didactic-formative experiment; capture possibilities and contradictions of the development of the study activity by the didactic experiment in the initial years of the students in a class in the early years of elementary school. The research problem was: school-age children (between 8, 9 and 10 years old) based on Davydov and Hedegaard's theories, are they able to form concepts and operate with them in a science study activity in a context of pedagogical intervention by the teacher? It was exposed as a research question: when it proposes the teaching of organized water content from the theory of developmental teaching and contributions of radical-local education by the double movement that has repercussions on students' learning in the early years in public schools? The research method was based on the form of theoretical-conceptual knowledge and dialectical thinking method. The main methodological procedure of research was the didactic-formative experiment, according to Davydov's guidance and Hedegaard's collaboration. The experiment took place in a municipal public school of SME, in Goiânia, with 31 students who attended Cycle I, Class C (3rd year of elementary school), oriented towards the formation of the concept "water" in science teaching. The results of the research indicated that the pedagogical intervention aimed at changes in mental procedures of the students towards the formation of theoretical thinking about the concept "water" partially corresponded to what was proved as a theoretical possibility. Specific changes were identified in part of the class of students, however, limitations related to institutional and sociocultural practices identified the comprehension of conventional pedagogical practices on the part of the teacher and insufficient provision of conditions on the part of the official school system for optimising pupils' learning, making it impossible to fully achieve the objectives set for the research